2020
DOI: 10.1097/jom.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

Work-to-Family Conflict and its Associations With Workers’ Burnout, Poor Self-Rated Health, and Minor Mental Disorder

Abstract: Objectives: To examine the distribution of work-to-family conflict (W-FC) across socio-demographic groups and a wide spectrum of occupations, and its associations with workers’ burnout, self-rated health, and mental health status by sex. Methods: A cross-sectional household survey of representative employees was conducted in 2013. A standardized questionnaire was administered to collect information. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…Different types of literature show that WFC is an essential factor affecting workers' physical and mental health [5,7,11]. Kahn et al (1964) defined WFC as ''the conflict and pressure between roles caused by the incompatibility between work and family roles" [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Different types of literature show that WFC is an essential factor affecting workers' physical and mental health [5,7,11]. Kahn et al (1964) defined WFC as ''the conflict and pressure between roles caused by the incompatibility between work and family roles" [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…High levels of WFCs can cause physical and mental stress and emotional exhaustion [14][15][16]. In terms of physical health, poor selfrated health (SRH) [8,11]; depression [17][18][19][20]; problem drinking behavior [15,18]; and physical symptoms such as fatigue, lack of appetite, and nervous tension are positively correlated [15,21,22]. Some investigators have found that a favorable workplace enables workers to balance their work and family roles, thereby reducing WFCs [8,14,[23][24][25].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations